Establishment of ultrasound-responsive SonoBacteriaBot for targeted drug delivery and controlled release - Du, Meng; Wang, Ting; Feng, Renjie; Zeng, Penghui; Chen, Zhiyi (Frontiers in Bioengineering and Biotechnology, 2023)
Bacteria-driven biohybrid microbots have shown great potential in cancer treatment. However, how precisely controlling drug release at the tumor site is still an issue. To overcome the limitation of this system, we proposed the ultrasound-responsive SonoBacteriaBot (DOX-PFP-PLGA@EcM). Doxorubicin (DOX) and perfluoro-n-pentane (PFP) were encapsulated in polylactic acid-glycolic acid (PLGA) to form ultrasound-responsive DOX-PFP-PLGA nanodroplets. Then, DOX-PFP-PLGA@EcM is created by DOX-PFP-PLGA amide-bonded to the surface of E. coli MG1655 (EcM). The DOX-PFP-PLGA@EcM was proved to have the characteristics of high tumor-targeting efficiency, controlled drug release capability, and ultrasound imaging. Based on the acoustic phase change function of nanodroplets, DOX-PFP-PLGA@EcM enhance the signal of US imaging after ultrasound irradiation. Meanwhile, the DOX loaded into DOX-PFP-PLGA@EcM can be released. After being intravenously injected, DOX-PFP-PLGA@EcM can efficiently accumulate in tumors without causing harm to critical organs. In conclusion, the SonoBacteriaBot has significant benefits in real-time monitoring and controlled drug release, which has significant potential applications for therapeutic drug delivery in clinical settings.